IMPLEMENTATION OF FLASK FOR STOCK CHECKING IN DISTRIBUTION CENTER & STORE ON MONITORING STOCK APPLICATION IN PT. XYZ - Alpha Adarrani Wibowo Putri; Yeremia Alfa Susetyo (Informatika, Universitas Jenderal Soedirman, 2022)
In a retail company stock control is a very important feature. Stock control that is done manually has many weaknesses especially for large companies that has many transactions in a day. This research aims to implement flask framework for control stock on the Monitoring Stock application at PT. XYZ. Flask framework was chosen because of its easy use and has a lot of libraries. The implementation of this flask framework uses the MVC architecture (Model, View, Controller). Then, it will be tested using box testing to ensure all features can run properly. Through the implementation of flask framework on the Monitoring Stock application, stock control at PT. XYZ can be more controlled so it can avoid losses due to stock miscalculations.